Growth kinetics of a diesel-degrading bacterial strain from petroleum-contaminated soil - Dahalan F.A.; Yunus I.; Johari W.L.W.; Shukor M.Y.; Halmi M.I.E.; Shamaan N.A.; Syed M.A. (Triveni Enterprises, 2024)
Indexed by WOS/Scopus